Should We Fix Them? A Comparison of Outcomes at Mid-Term Follow-Up of Operatively and Non- Operatively Treated Weber B Ankle Fractures - Laurence Ge MD; Paul G Talusan MD; James Holmes BA; David Walton MD (Foot & Ankle Orthopaedics, 2023)
Category: Trauma; Ankle Introduction/Purpose: Our group previously presented a novel protocol for non-operative management of Weber B ankle fractures with medial clear space (MCS) < 7mm on gravity stress (GS) radiographs and within 2mm of ipsilateral superior clear space and contralateral GS MCS. The goal of this study is to recruit an operative cohort for comparison of clinical, radiographic, and patient reported outcomes. Methods: We recruited a cohort of patients who may have been considered for the non-operative protocol but underwent surgery instead. Outcome measures were obtained including Kellgren-Lawrence scale for evaluation of arthritis, American Orthopedic Foot & Ankle Society (AOFAS) Hindfoot, Olerud Molander Ankle (OMA), Lower Extremity Functional Scale (LEFS), and PROMIS (physical function, depression, pain interference) scores. This data was then compared to the non-operative cohort. Results: There were 20 patients in the operative cohort and 29 in the original non-operative cohort. Mean follow-up was 6.9 and 6.7 years, respectively. Average outcome scores were as follows for the operative and non-operative groups, respectively: LEFS, 68.1 and 75.2 (p=0.009); OMA, 89.0 and 94.1 (p=0.05); AOFAS, 91.7 and 98.5 (p=0.0003); PROMIS Physical Function, 50.4 and 58.2 (p=0.01); PROMIS Depression, 45.4 and 42.8 (p=0.29); PROMIS Pain Interference, 49.7 and 42.2 (p=0.004). All patients in both groups achieved union of their fracture. There was no difference in Kellgren-Lawrence arthritis scores though interobserver reliability for scoring was poor. In the surgical cohort there were 3 (15%) cases of implant removal, 1 (%) SPN neurapraxia, and 1 (%) delayed wound healing. Conclusion: In carefully selected patients with isolated Weber B fractures and MCS < 7mm on gravity stress radiographs that is within 2mm of ipsilateral superior clear space and contralateral GS MCS, non-operative management may be considered as it can lead to equivalent or superior outcomes with none of the risks typically associated with surgical intervention.